2014
DOI: 10.1194/jlr.m050369
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal n-6 fatty acid metabolism in cystic fibrosis is caused by activation of AMP-activated protein kinase

Abstract: consistent alterations in PUFA metabolism ( 4-6 ). Consequently, CF patients have characteristic alterations in PUFA composition, including decreased levels of linoleic acid (LA) and DHA in blood, which are accompanied by increased arachidonic acid (AA) in tissues ( 7,8 ). The magnitude of these alterations correlates with disease severity, suggesting a link to pathophysiology ( 7,(9)(10)(11)(12).The PUFA alterations associated with CF have been recapitulated in models of CF. Both CFTR knockout ( 13,14 ) and ⌬… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Consistent with the above findings, our lipidomic analysis showed an increase in AA/LA and AA/DHA ratios in Cftr‐defective cells compared to their controls. Recent data showed that CFTR may alter AA/LA metabolism through an adenosine monophosphate–activated protein kinase–mediated increase in Δ5 and Δ6 desaturases . Altered AA/LA ratio and a lower production of DHA‐mediated endogenous activators of PPAR‐γ in CF biliary cells may account for the increased expression of the receptor as a compensatory mechanism to counteract a lower activation state.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the above findings, our lipidomic analysis showed an increase in AA/LA and AA/DHA ratios in Cftr‐defective cells compared to their controls. Recent data showed that CFTR may alter AA/LA metabolism through an adenosine monophosphate–activated protein kinase–mediated increase in Δ5 and Δ6 desaturases . Altered AA/LA ratio and a lower production of DHA‐mediated endogenous activators of PPAR‐γ in CF biliary cells may account for the increased expression of the receptor as a compensatory mechanism to counteract a lower activation state.…”
Section: Discussionmentioning
confidence: 99%
“…At least two studies using cultured respiratory epithelial cells have demonstrated increased activation of AMPK in CF compared with wild-type respiratory epithelial cells, as measured by increased phosphorylation of AMPKα and AMPK target acetyl CoA carboxylase (ACC) [ 59 , 60 ]. Furthermore, inhibition of AMPK activity normalized Δ5- and Δ6-desaturase expression and activity in CF cells to control cell levels [ 60 ]. Exogenous activation of AMPK had the opposite effect, increasing desaturase expression in wild-type cells to CF cell levels.…”
Section: Signalling Pathways Associated With Fatty Acid Abnormalitmentioning
confidence: 99%
“…However, while studies have shown no AMP excess in CF cells [ 59 ], there is clear evidence of alterations in Ca 2+ transport and metabolism, leading to increased Ca 2+ concentration in CF cells [ 63 , 64 ]. Accordingly, inhibition of CaMKKβ, either by a small molecule inhibitor or by Ca 2+ sequestration, resulted in normalization of desaturase expression and activity in CF cells [ 60 ]. These findings suggest that altered Ca 2+ metabolism and CaMKKβ activity are upstream of AMPK activation in CF.…”
Section: Signalling Pathways Associated With Fatty Acid Abnormalitmentioning
confidence: 99%
“…This increase in Δ5and Δ6-desaturase activity could be due to a loss of proper CFTR function, which leads to an increase in intracellular calcium that activates calcium/calmodulin-dependent protein kinase kinase β (CaMKKβ), which activates 5' AMP-activated protein kinase (AMPK). Inhibiting CaMKKβ or AMPK returns Δ5and Δ6-desaturase to control levels 19 . The decreased levels of DHA are likely due to increased retroconversion of DHA to its precursor molecule 20 .…”
Section: Lipid Imbalances In Cf Epitheliamentioning
confidence: 99%